THE RELATIONSHIP BETWEEN LEVELS OF ADOLESCENT KNOWLEDGE AND PREVENTION OF CLASS X CERVIC CANCER AT TAMAN SISWA PEMATANGSIANTAR HIGH SCHOOL 2019 - Nurmala; Ratih Angeli Pasaribu; Dewi Wandha Syahputri Daulay (RADJA PUBLIKA, 2022)
Cervical cancer is cancer that appears in cells in the cervix. Cervical cancer in Indonesia ranks second in the order of malignancy in women. The incidence of cervical cancer was 5,786 cases or 10.3% of other malignancies. In fact, around 500,000 women worldwide are diagnosed with cervical cancer and an average of 270,000 people die each year. The purpose of this study was to determine the level of knowledge of tenth grade girls at Taman Siswa Pematangsiantar High School, prevention of cervical cancer in tenth grade at Taman Siswa Pematangsiantar High School, and the relationship between the level of knowledge of young women and prevention of cervical cancer for class X at Taman Siswa Pematangsiantar High School. This research method is descriptive correlation through cross sectional approach, with a population of 100 and obtained 50 samples selected by purposive sampling and data collection for the dependent variable and independent variable was carried out simultaneously through a questionnaire instrument. The results showed that there were 36 respondents (72%) with good knowledge and 14 respondents (28%) with poor knowledge. Based on the results of the chi-square statistical test with a significance level of a = 0.05, a value of p = 0.01 was obtained, which means that there is a relationship between the level of knowledge and prevention of cervical cancer.